2019
DOI: 10.3982/ecta14474
|View full text |Cite
|
Sign up to set email alerts
|

Career and Family Decisions: Cohorts Born 1935-1975

Abstract: Comparing the 1935 and 1975 U.S. birth cohorts, wages of married women grew twice as fast as for married men, and the wage gap between married and single women turned from negative to positive. The employment rate of married women also increased sharply, while that of other groups remained quite stable. To better understand these diverse patterns, we develop a life-cycle model incorporating individual and household decisions about education, employment, marriage/divorce, and fertility. The model provides an ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 45 publications
5
43
0
Order By: Relevance
“…Our projection that college attainment will continue to increase in the United States is also consistent with Eckstein et al (2019). They develop a life cycle model to decompose how much of the increase in female college attainment-from less than 10 percent in 1960 to almost 40 percent in 2010, see the right panel of Figure 2-can be explained by changing labor and marriage market conditions versus changing preferences.…”
Section: Projections Of College Attainment Fertility and Longevity supporting
confidence: 73%
“…Our projection that college attainment will continue to increase in the United States is also consistent with Eckstein et al (2019). They develop a life cycle model to decompose how much of the increase in female college attainment-from less than 10 percent in 1960 to almost 40 percent in 2010, see the right panel of Figure 2-can be explained by changing labor and marriage market conditions versus changing preferences.…”
Section: Projections Of College Attainment Fertility and Longevity supporting
confidence: 73%
“…The model used in Eckstein, Keane and Lifshitz (2019) offered an explanation of women, who are willing to be employed after marriage under a circumstance of receiving a higher level of education. In addition, Juhn and McCue (2011) and Eckstein et al (2019) found that there was a declination of women's marriage rate. Based on Eckstein et al (2019) findings, this declination happened among younger-aged women and the key factor of this phenomena was the high maternal education.…”
Section: Women Marital Status (Mars)mentioning
confidence: 99%
“…An alternative approach would be to model fertility as a choice variable. Recent papers that estimate non-equilibrium life-cycle models with endogenous fertility decisions include Adda, Dustmann and Stevens (2017) and Eckstein, Keane and Lifshitz (2019). Both approaches allow younger women to have greater fertility capital.…”
Section: Fertility and Childrenmentioning
confidence: 99%
“…47 See Eckstein, Keane and Lifshitz (2019) for evidence on how the marriage wage premium has changed over time and the factors responsible for this. model does generate too high employment for single individuals over the life-cycle.…”
Section: Model Estimates and Fitmentioning
confidence: 99%
See 1 more Smart Citation